華埠通訊 Vol. 01, Issue 02, June 1993 - http://id.worldcat.org/fast/2009873 (1993)
Start of the newsletter with vol. 1, issue 1 in April of 1993. Published bi-monthly by the Chinese Consolidated Benevolent Association.